Individual and Neighborhood Factors Associated with Sexual Behavior Classes in an Urban Longitudinal Sample - Michele Green, Kerry (Sex Transm Dis, 2019)
BACKGROUND: This study aimed to increase understanding of the clustering of sexual behaviors in an urban sample of emerging adults, and the individual and neighborhood factors associated with sexual behavior patterns in order to provide insight into reducing the disproportionate burden of poor sexual outcomes among urban African Americans. METHODS: We draw on two cohorts of urban, predominantly African American youth first assessed at age 6 and follow-up to emerging adulthood (mean age 20, n=1,618). Latent class analyses by gender identified co-occurrence of sexual behavior. RESULTS: We found three classes for both males and females: high-risk (13% of males, 15% of females), low-risk (54% of males, 56% of females) and no-risk (33% of males, 29% of females). Membership in the high-risk class was associated with school dropout, a substance use disorder diagnosis, having a criminal arrest, pregnancy, and STDs for both males and females. High-risk females also had higher rates of depression. Low-risk males and females also had elevated risk of pregnancy and parenthood. Neighborhood factors distinguished the high- and no-risk classes for males and females, including the neighborhood environment scale, which assessed poverty, safety, drug activity, and crime/violence in the neighborhood. Neighborhood religiosity was inversely associated with membership in the high-risk class compared to the no-risk class for females only. Neighborhood racism distinguished those in the high-risk class compared to the no-risk class for males. CONCLUSION: Future work should take into account the clustering of sexual risk behaviors. Specific neighborhood factors could be addressed to reduce sexual health disparities.